2017
DOI: 10.1111/1365-2656.12669
|View full text |Cite
|
Sign up to set email alerts
|

Climatic variation modulates the indirect effects of large herbivores on small‐mammal habitat use

Abstract: Large mammalian herbivores (LMH) strongly shape the composition and architecture of plant communities. A growing literature shows that negative direct effects of LMH on vegetation frequently propagate to suppress the abundance of smaller consumers. Indirect effects of LMH on the behaviour of these consumers, however, have received comparatively little attention despite their potential ecological significance. We sought to understand (i) how LMH indirectly shape small-mammal habitat use by altering the density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 90 publications
2
19
1
Order By: Relevance
“…Keesing showed that the exclusion of large herbivores in KLEE led to a rapid and sustained doubling of small‐mammal abundance. Subsequent research in UHURU has revealed a pattern that is congruent with, and of similar magnitude to, Keesing's results . These effects appear to stem chiefly from exploitation competition: the release of herbivorous and omnivorous rodents from competition for food 59 —especially seeds, which are the primary food for the dominant small‐mammal species, and the production of which is suppressed by ungulate herbivory .…”
Section: Lesson #3: Lmh Play Central Roles In Trophic Cascades and Otsupporting
confidence: 59%
“…Keesing showed that the exclusion of large herbivores in KLEE led to a rapid and sustained doubling of small‐mammal abundance. Subsequent research in UHURU has revealed a pattern that is congruent with, and of similar magnitude to, Keesing's results . These effects appear to stem chiefly from exploitation competition: the release of herbivorous and omnivorous rodents from competition for food 59 —especially seeds, which are the primary food for the dominant small‐mammal species, and the production of which is suppressed by ungulate herbivory .…”
Section: Lesson #3: Lmh Play Central Roles In Trophic Cascades and Otsupporting
confidence: 59%
“…It is also possible that S. mearnsi could be drawn to the greater availability of seeds of forbs and particularly Acacia spp., living trees of which were denser on the unburned plots a few years after the fire (Long et al. ), although body mass was the same for this species on burned as unburned patches.…”
Section: Discussionmentioning
confidence: 95%
“…, Long et al. ). Similarly, enhanced insect availability and enhanced visual cover may explain why 14 of 15 captures of the diurnal insectivore E. rufescens were inside or adjacent to exclosures in red sands.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found a significant rainfall × land‐use interaction, with rainfall affecting the responses of small mammal in agricultural and pastoral areas but not in areas without agriculture or livestock. Long et al () detected an interaction between large herbivores and rainfall on habitat selection by small mammals in Kenya. That study pooled captures of three species of small mammals, from both bare ground and tree‐covered patches, in plots that were either accessible to large herbivores or from which large herbivores had been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic factors, such as the introduction or range expansion of a non-native plant species, can also alter the indirect interactions between consumers in the invaded areas (Pearson, 2009). The consequences of indirect interactions can also depend on climatic conditions that shift over time (Brown et al, 2001;Heske, Brown, & Mistry, 1994;Long, Wambua, Goheen, Palmer, & Pringle, 2017). This variability in outcomes, combined with the rapidly changing global climate (Rosenzweig et al, 2008) and the increasing prevalence of exotic species in ecosystems (Hellmann, Byers, Bierwagen, & Dukes, 2008;Rosenstock, 1996), make long-term experiments of critical importance for examining context-dependent interactions among consumers.…”
Section: Introductionmentioning
confidence: 99%